2019
DOI: 10.1109/tcomm.2019.2907623
|View full text |Cite
|
Sign up to set email alerts
|

NOMA-Based Compressive Random Access Using Gaussian Spreading

Abstract: Compressive random access (CRA) is a random access scheme that has been considered for massive machine-type communication (MTC) with non-orthogonal spreading sequences, where the notion of compressive sensing (CS) is used for lowcomplexity detectors by exploiting the sparse device activity.In this paper, we study the application of power-domain nonorthogonal multiple access (NOMA) to CRA in order to improve the performance of CRA (or increase the number of devices to be supported). We consider Gaussian spreadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In [149], a joint sub-carrier and transmission power allocation problem were considered and solved to maximize the number of MTC devices and satisfy the transmission power constraints. In [150], NOMA to cGFRA was adopted to improve the performance of cGFRA and it was revealed that the number of incorrectly detected device activity can be reduced by applying NOMA to cGFRA. In [151], a low-complexity dynamic cGFRA for NOMA was proposed to jointly realize user activities and data detections.…”
Section: B Noma Based Iot Connectivitymentioning
confidence: 99%
“…In [149], a joint sub-carrier and transmission power allocation problem were considered and solved to maximize the number of MTC devices and satisfy the transmission power constraints. In [150], NOMA to cGFRA was adopted to improve the performance of cGFRA and it was revealed that the number of incorrectly detected device activity can be reduced by applying NOMA to cGFRA. In [151], a low-complexity dynamic cGFRA for NOMA was proposed to jointly realize user activities and data detections.…”
Section: B Noma Based Iot Connectivitymentioning
confidence: 99%
“…By using NOMA, additional users, such as delay-tolerate devices, can be admitted to the channel. As a result, the overall spectral efficiency is improved, and the use of advanced forms of NOMA can ensure that massive connectivity is supported while strictly guaranteeing all devices' QoS requirements [5]- [7]. It is worth to point out that successive interference cancellation (SIC) is a key component of NOMA systems, and conventionally SIC decoding orders are mainly determined by the devices' channel state information (CSI).…”
Section: A Motivations and The Related Existing Workmentioning
confidence: 99%
“…The author in [3] has shown that a promising solution to support massive uplink connectivity for short packet transmission is the Gaussian multiple access channel (G-MAC). The challenging task in the realization of G-MAC is the design of efficient and low complexity multiuser detection (MUD) algorithms at the base station (BS) to achieve the desirable spectral efficiency and reliability for short-packet transmission [4].…”
Section: Introductionmentioning
confidence: 99%